Evaluation of Business Strategy Using The Servo Analysis Method - Ebenezer, Alfred; Aryati, Ana Sofia (Jurnal Kewirausahaan dan Inovasi, 2025)
The development of the aviation industry in Indonesia is quite behind when compared to some neighboring countries, therefore strategy evaluation is needed to help the development of the aviation industry in Indonesia. The objective of this research is to identify the conditions of PT GMF AeroAsia in terms of business strategy, business environment, resource usage method, organizational value management method, and the way the company runs as an organization. The data was harvested from interviews with relevant informants regarding the company’s annual reports and from the public-expose dialog conducted by the company, which is accessible through the website of Indonesia Stock Exchange as the accountability report of PT GMF AeroAsia for their shareholders. The results of the analysis demonstrate that strategy, environment, and resource at PT GMF AeroAsia are mutually-influencing elements, that value is the element with the weakest influence or is influenced by other elements, and that organization is a quite influential element although its strength is not as high as the strength of the earliest three elements. One of the implications that occurred when the research was conducted was that the location of the research object inside the airport area made the researcher unable to get full access when conducting observations.